2017
DOI: 10.1111/ijfs.13371
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐proliferative activity of bovine blood hydrolysates towards cancer cells in culture

Abstract: Four proteins, α/β globulin, serum albumin, γ‐globulin and fibrinogen, were isolated from bovine blood and hydrolysed using papain. Hydrolysates were assessed for non‐cellular and cellular antioxidant activity. The anti‐proliferative activity of hydrolysed fractions was assessed in a number of cancer cell lines including U937 lymphoma cells, MCF‐7 breast cancer cells, HepG2 hepatocytes and Caco‐2 epithelial colorectal adenocarcinoma cells. Anti‐inflammatory activity of the hydrolysates was also assessed. Hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…Following on from these studies, oxidative DNA damage was induced in cells using H 2 O 2 at a concentration of 80 μmol L −1 for 30 min. Previously published studies using the comet assay have employed similar concentrations of H 2 O 2 with U937 cells (Crowley et al, ; O'Sullivan, Lafarga, Hayes, & O'Brien, ).…”
Section: Methodsmentioning
confidence: 99%
“…Following on from these studies, oxidative DNA damage was induced in cells using H 2 O 2 at a concentration of 80 μmol L −1 for 30 min. Previously published studies using the comet assay have employed similar concentrations of H 2 O 2 with U937 cells (Crowley et al, ; O'Sullivan, Lafarga, Hayes, & O'Brien, ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, several studies have demonstrated the potential of blood proteins for use as technofunctional ingredients and as novel sources of bioactive peptides. For example, O'Sullivan, Lafarga, Hayes and O'Brien () recently suggested the potential of papain (EC 3.4.22.2) hydrolysates of bovine blood proteins as antiproliferative agents using a number of cancer cell lines including U937 lymphoma cells, MCF‐7 breast cancer cells, HepG2 hepatocytes, and Caco‐2 epithelial colorectal adenocarcinoma cells.…”
Section: Common Bovine and Porcine Co‐products With Potential For Thementioning
confidence: 99%
“…In this study, no significant effects on the antiproliferative properties of the extracts were observed after a simulated gastrointestinal digestion. In addition, Castro, Maria, Bouhallab, and Sgarbieri () suggested the antitumoral potential of an enzymatic hydrolysate of porcine collagen on murine hepatoma cells and O'Sullivan et al () demonstrated the potential of papain hydrolysates of bovine blood proteins as antiproliferative agents using a number of cancer cell lines.…”
Section: Biologically Active Peptides Generated From Bovine and Porcimentioning
confidence: 99%
“…Protein hydrolysates from food have shown multiple bioactivities, for example anticancer, antioxidant, mineral binding, antimicrobial, antihypertensive and immunomodulatory effects (Girón‐Calle et al ., ; García Fillería & Tironi, ; Sae‐leaw et al ., ; Li‐Chan, ; O'Sullivan et al ., ). Numerous protein hydrolysates and peptides with anticancer effects on colon cancer cells have been obtained from chickpea (Girón‐Calle et al ., ), soya bean (Rayaprolu et al ., ) and rice (Kannan et al ., ).…”
Section: Introductionmentioning
confidence: 97%